Polygenic hazard score is associated with prostate cancer in multi-ethnic populations - Minh-Phuong Huynh-Le (Nature Portfolio, 2021)
A polygenic hazard score (PHS1) improves prostate cancer screening accuracy in European patients. Here, the authors test the performance of a version compatible with OncoArray genotypes (PHS2) in a multi-ethnic dataset and find that it risk-stratifies men for any, aggressive, and fatal prostate cancer.